Batas Waktu Pelaksanaan Eksekusi Pidana Mati di Indonesia: Komparasi Kepastian Hukum dan Hukum Pidana Islam - Nada Lia Wulandari; Ruslan Abdul Ghani; Rahmi Hidayati Al Idrusiah (IAIN Langsa, 2026)
This study aims to examine the implementation of the death penalty in Indonesia and the time limit for carrying out executions under Law No. 1 of 2023, as well as to analyze the perspective of Islamic criminal law on the death penalty in Indonesia. This article constitutes qualitative library research. The methodology employed is a normative juridical study using conceptual and comparative approaches. The findings indicate that prior to the execution of the death penalty, several legal remedies are available in Indonesia, namely appeal, cassation, judicial review, and the submission of clemency to the President. Furthermore, the execution of the death penalty must be carried out within a maximum period of one year after the rejection of clemency. The study suggests the need for regulatory reform concerning the time limit for implementing the death penalty in Indonesia, including amendments to the Law on Clemency, considering that Islamic criminal law likewise does not stipulate a specific time limit for the execution of the death penalty, similar to the Indonesian criminal law system.